On the stability of shield-driver circuits - Spinelli, Enrique Mario (2010)
This paper analyzes the stability of shield-driver circuits (SDCs) applied to the measurement of remote signal sources (such as bioelectric signals) and then proposes design ideas to guarantee it. According to the performed analysis, there are at least two factors that explain the potential instability of the SDC: 1) a high order of the SDC transfer function and 2) the parasitic inductance of the interconnecting cable. The former makes the circuit unstable for intermediate values of the output resistance RS of the signal source, whereas the latter makes the circuit unstable for low values of RS. These theoretical predictions are experimentally validated using several commercial operational amplifiers.